Imaging of the Vocal Tract based on Magnetic Resonance Techniques - Sandra Ventura (2010)
Magnetic resonance (MR) imaging has been used to analyze and evaluate the vocal tract shape through different techniques and with promising results in several application fields. Our main purpose is to demonstrate the relevance of MR and techniques of image processing in the analysis of vocal tract. The extraction of contours of the air cavities from 2D images (slices) allowed the built of several 3D reconstruction image stacks by the combination of orthogonally oriented sets of slices for each articulatory gesture, as a new approach to solve the expected spatial under sampling of the imaging process. In result, these computational models provide valuable information for the enhanced visualization of morphologic and anatomical aspects and are useful for partial measurements of the vocal tract shape in different situations. Potential use of this information can be found in Medical and therapeutic applications as well as in acoustic articulatory speech modeling.